Fat Reduction Efforts: A 24-Month Longitudinal Comparison of a Large Sample of Maintainers, Relapsers, and Non-Changers. Issue 1 (January 2016) - Yusufov, Miryam; Paiva, Andrea L.; Redding, Colleen A.; Lipschitz, Jessica M.; Gokbayrak, N. Simay; Greene, Geoffrey; Rossi, Joseph S.; Blissmer, Bryan; Velicer, Wayne F.; Prochaska, James O.
This research examined dynamic transtheoretical model (TTM) constructs for dietary fat reduction. This secondary data analysis pooled three large population-based TTM-tailored school, worksite, medical, and home-based intervention studies and examined use of constructs across three groups organized by longitudinal progress (dynatypes): Maintainers, Relapsers, and Stable Non-Changers. The criteria for successful change, at the time, were that less than 30% of calories came from fat. A total of 2, 718 adults met criteria for an unhealthy diet at baseline. The majority of participants were female, White, married, and middle-aged. Demographics, Stage of Change, Processes of Change, Decisional Balance, and Temptations were measured. Dynatype groups were assessed with reliable and valid scales assessing constructs at baseline and 6, 12, and 24 months. Analyses included a multivariate analysis of variance followed by a series of analyses of variance, with Tukey follow-up tests assessing differences in use of TTM constructs across the three groups at each time point. Relapsers and Maintainers were similar in their use of all TTM Processes of Change at baseline, with the exception of Self-Liberation (η 2 = 0.15, p < .001) and Reinforcement Management (η 2 = 0.01, p < .001). Although Relapsers reverted to an unhealthy diet, their overall greater use of Processes of Change suggests that their behaviors and strategy use remain better than that of the Stable Non-Changer group. Results suggest that specific cognitive and behavioral constructs may contribute differentially to intervention outcomes.